2022
DOI: 10.1111/jocd.15559
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma protects human keratinocytes from UVB‐induced apoptosis by attenuating inflammatory responses and endoplasmic reticulum stress

Abstract: Due to increased outdoor activities, diversified styles of clothes, prolonged human life span, and depleted ozone, people are forced to expose to stronger ultraviolet (UV) for longer time. 1,2 If the skin is exposed to sunlight for a long time, beyond the threshold of UV light that the skin can withstand, the skin can be damaged and photoaging phenomena may ensue. 3,4 Photoaging mainly refers to the process of skin aging caused by extrinsic factors such as UV light, smoking, and exposure to chemicals. In the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The effect was mediated by upregulated extracellular signal-regulated kinase cascade 1/2 (ERK1/2) and protein kinase B (Akt) signal pathways, with reduced intracellular oxidation [ 67 ]. Such observations join other reports unrelated to reproductive biology [ 5 , 61 , 67 ] where metabolic spoliation was erased following PRP dosing. The question of similar PRP effects in the adult human ovary seems answered, for now, only by small series and case reports [ 42 , 43 , 44 ].…”
Section: Prp and Organ Damage Reversalsupporting
confidence: 88%
See 1 more Smart Citation
“…The effect was mediated by upregulated extracellular signal-regulated kinase cascade 1/2 (ERK1/2) and protein kinase B (Akt) signal pathways, with reduced intracellular oxidation [ 67 ]. Such observations join other reports unrelated to reproductive biology [ 5 , 61 , 67 ] where metabolic spoliation was erased following PRP dosing. The question of similar PRP effects in the adult human ovary seems answered, for now, only by small series and case reports [ 42 , 43 , 44 ].…”
Section: Prp and Organ Damage Reversalsupporting
confidence: 88%
“…One major event during apoptosis is the escape of cytochrome-C (cyt-C), a highly conserved mitochondrial hemeprotein vital to electron transport and cellular respiration [ 60 ]. Transit of cyt-C into cytosol can occur through a membrane channel controlled by the first regulator of apoptosis to be identified in any organism, Bcl-2.61 Bcl-2 thus exerts an anti-apoptotic function by conserving membrane potential via blocking release of cyt-C [ 61 , 62 ]. While PRP can induce proliferation of Bcl-2 with therapeutic effects resulting from significant declines in cyt-C [ 61 ], this awaits full characterization in the adult human ovary.…”
Section: Subcellular Characteristics After Prpmentioning
confidence: 99%
“…Here, to validate the synergistic anti-tumor efficacy of TET-CTM/L, all celastrol treatments including CEL, CEL+TET, CTM, and TET/L were taken as controls, our study evaluated the cytotoxicity of TET-CTM/L against HepG2 cells. 41 , 42 All various celastrol treatments had obvious proliferation inhibition of HepG2 cells, meanwhile we found that the intensity of proliferation inhibition increased significantly with the increase in celastrol concentration after treatment for 24 and 48 h ( Figure 3C and D ). The IC 50 values of various celastrol treatments against HepG2 cells for 24 h were 3.31 ± 0.64, 2.99 ± 0.48, 9.04 ± 0.88, 34.47 ± 1.63, 8.89 ± 0.55 μg/mL, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…RNAseq further identified the downregulated genes related to cell replication [33]. In contrast, some found that platelet-rich plasma increased the proliferation of human HaCaT keratinocytes [34], while others found no relevant change in HaCaT proliferation [35]. Considering dentistry, platelet-rich stimulated the proliferation of SCC25 epithelial-like cells originally isolated from the tongue of a patient with squamous cell carcinoma [14], while PRF decreased the viable cell number using an MTT assay of an oral epithelial cell line derived from a gingival carcinoma and metastasis to the cervical lymph node [36].…”
Section: Discussionmentioning
confidence: 99%